Challenges, Opportunities, and Prospects of Applying Innovative Technologies and Artificial Intelligence in the Reconstruction and Development of Ukraine (Global Journal of Human-Social Science, 2024)
The publication is dedicated to the analysis of the role of innovative technologies and artificial intelligence in the post-war recovery process of Ukraine The relevance of the research is driven by the necessity for rapid and effective recovery of the economy social sphere and industry after significant destruction caused by military actions The paper examines the main economic and social problems caused by the war as well as the state of the industrial sector and its modernization It analyzes existing innovative technologies their application in industry the possibilities of using AI to optimize production processes and resource management The effectiveness of AI in predicting and minimizing chaotic phenomena in socio-economic systems is evaluated Methods for integrating advanced technologies into production processes are proposed and the impact of digitalization and automation on increasing productivity and reducing costs is studied The use of energy-efficient technologies and materials is considered and the impact of implementing green technologies on environmental safety is assessed Mechanisms for involving the public in innovative development are identified and the impact of public participation on the effectiveness of implementing innovative projects is evaluated Existing programs and initiatives to support innovation and scientific research as well as opportunities for international cooperation in the field of innovation and technology are analyzed The research results show that the integration of advanced technologies and innovative practices contributes to accelerating technological development enhancing the competitiveness of Ukrainian enterprises in the global market modernizing infrastructure increasing investments creating new jobs reducing environmental impact and ensuring sustainable development of Ukraine
Keywords: innovative technologies; artificial intelligence; restoration of Ukraine; industry; digitalization; energy efficiency